Rhetor response : a theory and practice of literary affordance - Khost, Peter H. (Utah State University Press, 2018)
"Bridging the disciplinary divide between writing and literature and introducing the concept of "literary affordances"--A theory that addresses interpretation and use through understanding how a rhetor applies a text. A mix of rhetorical theory, literary criticism, pedagogical manifesto, political treatise, and psychological and philosophical memoir"--Provided by publisher